SISTEM INFORMASI PENGADUAN DAN PENGAJUAN IKLAN LAYANAN BERBASIS WEBSITE DI DISKOMINFO JOMBANG - Anggreani, Nilam Kumallah; Kartika, Dhian Satria Yudha; Najaf, Abdul Rezha Efrat (JURNAL ILMIAH INFORMATIKA, 2024)
The development of information technology has been utilized by the Communication and Informatics Office of Jombang Regency to enhance the efficiency of public services in the process of receiving complaints and submissions. However, the system in use still faces challenges such as suboptimal response speed, lack of transparency, and difficulties in data storage as some still use email and Google Forms as the mediums for receiving complaints and submissions. The prototype method was used in the development of this system. The stages include communication, quick planning, quick design modeling, construction of the prototype, and deployment, delivery, and feedback. This research resulted in a complaint and public service advertisement submission information system that can facilitate the public in the process of submitting complaints, submission requests, and data collection and management by the admin.